2019
DOI: 10.1038/s41467-019-08863-1
|View full text |Cite
|
Sign up to set email alerts
|

SFPQ and NONO suppress RNA:DNA-hybrid-related telomere instability

Abstract: In vertebrates, the telomere repeat containing long, non-coding RNA TERRA is prone to form RNA:DNA hybrids at telomeres. This results in the formation of R-loop structures, replication stress and telomere instability, but also contributes to alternative lengthening of telomeres (ALT). Here, we identify the TERRA binding proteins NONO and SFPQ as novel regulators of RNA:DNA hybrid related telomere instability. NONO and SFPQ locate at telomeres and have a common role in suppressing RNA:DNA hybrids and replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 56 publications
5
84
0
Order By: Relevance
“…Some of the proteins bound to TERRA or RNA:DNA hybrids may act to reduce replication stress and suppress ALT. For example, TERRA -binding proteins SFPQ and NONO suppress telomeric RNA:DNA hybrids, and depletion of SFPQ increases APBs and telomere recombination in ALT + cells [80].…”
Section: Regulatory Circuitries Of Altmentioning
confidence: 99%
“…Some of the proteins bound to TERRA or RNA:DNA hybrids may act to reduce replication stress and suppress ALT. For example, TERRA -binding proteins SFPQ and NONO suppress telomeric RNA:DNA hybrids, and depletion of SFPQ increases APBs and telomere recombination in ALT + cells [80].…”
Section: Regulatory Circuitries Of Altmentioning
confidence: 99%
“…More recently, further involvement of SFPQ in the maintenance of genome stability has been demonstrated in relation to telomere maintenance, where the SFPQ/NONO heterodimer has been identified as a novel regulator at telomeres [ 46 ] ( Figure 2 E). It was shown that loss of SFPQ/NONO results in a significant increase in telomere recombination events and rapid alterations in telomere length in both telomerase-positive and negative cells.…”
Section: The Rna-binding Protein Sfpqmentioning
confidence: 99%
“…As positive controls, we used 5 pairs of RBPs that were detected in our screen and that had a least 5 independent literature sources in BioGRID confirming direct interaction (U2AF1-U2AF2; FMR1-FXR2; HNRNPK-QKI; RBFOX2-QKI; and SFPQ-NONO). In most cases, these pairs are also known to act as heterodimers and bind RNA as a complex (Fernandez et al, 2015;Li et al, 2018;Petti et al, 2019;Wu et al, 1999). As negative controls, we used randomly generated sets of RBP pairs of the same size as the screen hits.…”
Section: Direct Binary Rbp Interactions Predict Combinatorial Rna Binmentioning
confidence: 99%